Perilous waters: early maritime trade along the western coast of the Black Sea (fifth millennium Bc) - Ivanova-Bieg, Maria (Oxford journal of archaeology, 2012)
A heavy accumulation of exotica and valuables, such as gold, copper, carnelian and Mediterranean shells, distinguishes the Black Sea littoral from other parts of the east Balkans in the fifth millennium BC.1 Recent discoveries shed new light on the trading connections of the coastal communities and indicate that maritime activity was germane to the origin of their extraordinary wealth. This article investigates the involvement of the coastal inhabitants with the sea. It addresses the ecological conditions and the technical parameters of prehistoric seafaring on the west coast of the Black Sea, considers the remains of marine species in the faunal record as an indication of maritime experience, and examines the artefactual record for signs of movement of goods and people between the coastal communities. The combination of these separate lines of evidence points to a maritime trading route joining the resource-poor north with the resource-rich south of the littoral in the Chalcolithic period. Moreover, it implies that sea-borne trade not only enabled the accumulation of material wealth, but also was pivotal for social change.
Gesehen am 21.11.2018